Preparing Analytics-Enabled Professionals in Finance Using a Simultaneous Team-Teaching Approach: A Case Study - Katie A. McCarthy; Gregory A. Kuhlemeyer (Journal of Statistics and Data Science Education, 2024)
AbstractTo meet the demands of industry, undergraduate business curricula must evolve to prepare analytics-enabled professionals in fields such as finance, accounting, human resource management, and marketing. In this article, we provide a case study of developing a rigorous, integrated finance and data analytics course that was delivered using a simultaneous team-teaching approach within a regional, teaching university. This case study describes developing the learning outcomes; defining the integrated teaching approach; identifying and developing course content and materials; and planning the course delivery. Next, we describe the course delivery, including student achievement of course learning outcomes, and a summary of student feedback from end-of-course evaluations is provided. Finally, we present lessons learned from delivering the course and provide considerations for future work such as scaling this course and replicating it in other business domains.